2014
DOI: 10.3961/jpmph.2014.47.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Control Programs in East Asia: Evidence From the International Literature

Abstract: Cancer is a major cause of mortality and morbidity throughout the world, including the countries of North-East and South-East Asia. Assessment of burden through cancer registration, determination of risk and protective factors, early detection and screening, clinical practice, interventions for example in vaccination, tobacco cessation efforts and palliative care all should be included in comprehensive cancer control programs. The degree to which this is possible naturally depends on the resources available at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Helicobacter pylori infection is a well-established risk factor for gastric cancer, and the International Agency for Research on Cancer has classified it as a class I carcinogen for gastric cancer (Brenner et al, 2009;Ford et al, 2014;Moore, 2014). As would be expected, helicobacter pylori infection is generally more prevalent in countries with high gastric cancer incidence rates than countries with low gastric cancer incidence rates (Fock, 2014).…”
Section: Overviewmentioning
confidence: 71%
See 2 more Smart Citations
“…Helicobacter pylori infection is a well-established risk factor for gastric cancer, and the International Agency for Research on Cancer has classified it as a class I carcinogen for gastric cancer (Brenner et al, 2009;Ford et al, 2014;Moore, 2014). As would be expected, helicobacter pylori infection is generally more prevalent in countries with high gastric cancer incidence rates than countries with low gastric cancer incidence rates (Fock, 2014).…”
Section: Overviewmentioning
confidence: 71%
“…Smoking is a causal risk factor for gastric cancer and it is estimated that about one in six gastric cancers are attributable to smoking (Gonzalez et al, 2003;LadeirasLopez et al, 2008;Brenner et al, 2009;Moore, 2014). There is also an established link between a high dietary salt intake and gastric cancer and a recent meta-analysis of prospective studies found a relative risk of 1.68 (95% confidence interval: 1.17-2.41) for high versus low salt intakes (D'Elia et al, 2012;D'Elia et al, 2014;Moore, 2014).…”
Section: Modifiable Gastric Cancer Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, many reports highlight the increasing trend in breast cancer incidence in developed countries and many of which have been detected in advanced stages where the cure is not possible [ 1 ]. Lifestyle (carcinogens, alcohol, tobacco, post-menopausal obesity and less exercise), reproductive factors (early menarche, late menopause, hormone level, and pregnancy) and diet with high-fat content have been established as the common risk factors for breast cancer development especially in asian population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early efforts have reported several challenges including the lack of access to care, contamination of the environment, and cancer fatalistic attitudes among individuals in China, lack of informed healthcare staff, and sociocultural barriers in India, and inadequate assessment of cancer burden, negative societal attitudes towards cancer prevention, and lack of partnerships and engagement in Russia [66]. Many countries (both developed and developing) have cited the need for better assessments of cancer burden, determination of risk and protective factors, early detection and screening, interventions in vaccination, tobacco cessation efforts and palliative care, coordination and measurement of impact [67,68]. The U.S. NCCCP provides a successful model, addressing all these factors in a coordinated, impactful, and collaborative approach for these countries to learn from and adapt.…”
Section: Resultsmentioning
confidence: 99%